Pola Asuh Orang Tua Mempengaruhi Perilaku Picky Eater Pada Anak Prasekolah - Ribkha Itha Idhayanti; Anggit Puspitaningrum; Arfiana Arfiana; Munayarokh Munayarokh; Mundarti Mundarti (Midwifery Care Journal, 2022)
Picky eater is a child with picky eating behavior, doesn't want to eat, or only likes certain food variations, one of the problems in children that really needs to be considered by parents and health workers, because this picky eating behavior has a detrimental effect on children. General objective: to find out the relationship between parenting patterns and picky eater behavior in preschool children. This research was conducted in Manggis Village, Lekosno District, Wonosobo Regency. This type of research is a quantitative research type using a cross sectional approach. The sampling technique used is the slovin formula and then random slamping is performed. Univariate analysis used the frequency distribution of the percentage of each variable, and bivariate analysis used Spearman rank correlation. The results: the results of the sperm rank correlation test obtained a Sig. (2-tailed) value of 0.000, the correlation coefficient of 0.603* means that there is a significant relationship between parenting patterns and picky eater behavior in preschool children with the level of correlation strength or relationship. is a strong relationship. The majority parenting pattern is democratic as much as 46.2%, permissive 30.8%, authoritarian 15.4%, and nacglet 7.7%. The behavior of pre-school age children in Manggis Village has the majority of picky eater behavior as many as 21 respondents or 53.8%, and those who do not have picky eater behavior as many as 18 respondents or 46.2%. There is a significant relationship between parenting patterns and picky eater behavior of preschool children